James L. Hansen letter to Thomas H. Kent regarding spring bird sightings and accompanying field notes, June 1, 1983 - Hansen, James L.et al (1983)
Letter with accompanying field notes from James L. Hansen to Thomas H. Kent regarding spring bird sightings in north central Iowa, June 1, 1983. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1983. Epson - sheet feed